Ad astra [videorecording (DVD)] - Gray, James, 1969-; Pitt, Brad, 1963-; Jones, Tommy Lee, 1946-; Elise, Kimberly, 1971-; Tyler, Liv; Sutherland, Donald, 1935- (20th Century Fox Home Entertainment, 2019)
Army Corps engineer and astronaut Roy McBride is searching for answers in the depths of space. Twenty years ago, Roy's father went in search of proof of the existence of extraterrestrial life on Neptune during a one-way mission. The mission was designated officially as a failure. Roy searches the solar system for the truth about both his father's mission and a recent mystery that has unfolded that threatens Earth. What Roy doesn't know is that this journey will do more than test him physically and mentally. The answers he finds will challenge everything he understands about the existence of humans.